Influence Of Silica Content into Nickel/Silica Electrodeposited Composite Coating for Mechanical and Corrosion Resistant Properties Enhancement: A Review - Koutouan Désiré Martial Abro; Adjoavi Colette Djassou; Yao Joseph Adjoumani; Kouassi Benjamin Yao (Indonesian Journal of Chemical Research)
The ratio cost/efficiency of electrodeposited composite coating has boosted the development of this method in the last decades.  Thus, electrodeposited nickel with silica particles as reinforcement was successfully designed and the conditions to increase particles in the composite are better understood. Those composites' morphological, mechanical, and corrosion properties as a function of the embedded silica particles were also investigated. In this review, the last findings about nickel/silica preparations and their properties are specifically summarized. Data collected here indicate that silica particles entrapment depends on current density, particle load in the bath, particle surface modification, and hydrodynamics. The presence of silica particles in the composite led to the refinement of the nickel grain and consequently enhanced the mechanical and corrosion properties.